Scientific Approach in Imparting Islamic Values In Early Childhood: A case study in Raudatul Aisyiyah Athfal Baubau - Slamet, Agus; Kurniati, Asma (Institut Agama Islam Negeri Imam Bonjol Padang, 2018)
This study aims to describe the planting of Islamic values through a scientific approach in early childhood.Â This research was descriptive with qualitative research belongs to the type of case studies conducted in Raudatul Aisyiyah Athfal Wale Wolio Baubau, Southeast Sulawesi. Aspects that are studied are internalizing the values of islam to cultivate gratitude as a creature of Gods creation and care for the environment, through the stages of scientific approaches, namely: to observe, ask yourself, menalar, try, and communicate. Researchers acted as a means of collecting the data, and using the tools in the form of guidelines for observation and interview guidelines are summarized in the form of the note field and tools documentation. The results showed that the cultivation of the values of islam through a scientific approach in early childhood can be done by providing knowledge and experience in early childhood, beginning with shows the power of the Almighty God who created living things, cultivate a sense of gratitude for existence and benefits of the creatures of his creation, as well as how to treat the creature creation.